Corporate Responsibility for Hazardous Waste Pollution Based on Environmental Regulations - Asyfa Prasasti; Wahyu Nugroho; Hartinie Abd Aziz (Universitas Islam Negeri Walisongo Semarang, 2025)
Industrial development has significantly contributed to national economic growth; however, it has simultaneously posed serious ecological risks due to inadequate management of hazardous and toxic waste. Although a robust legal framework exists—primarily through Law No. 32 of 2009 on Environmental Protection and Management and Government Regulation No. 101 of 2014 on Hazardous and Toxic Waste Management—the weak enforcement of corporate accountability mechanisms in practice has further complicated this issue. Accordingly, this article examines corporate legal responsibility for environmental pollution caused by hazardous and toxic waste within the framework of Indonesia’s environmental law. Employing a juridical-empirical method through statutory, conceptual, and case study approaches, the research analyzes the application of legal doctrines such as the polluter pays principle, strict liability, vicarious liability, and identification theory in enforcing corporate accountability for environmental pollution. The findings reveal that most companies have failed to comply with waste management standards due to weak supervision, regulatory ambiguity, and inconsistent sanctions, resulting in recurring environmental violations. Only a small number of corporations have been effectively held accountable under civil, administrative, or criminal law. Therefore, strengthening regulatory harmonization, improving the effectiveness of law enforcement, and integrating corporate responsibility principles are urgent measures for achieving sustainable industrial governance. Ultimately, a transparent and stringent accountability framework serves as a key instrument for upholding the polluter pays principle while safeguarding public health and environmental sustainability. Pembangunan industri telah memberikan kontribusi yang signifikan terhadap pertumbuhan ekonomi nasional, namun di sisi lain menimbulkan risiko ekologis yang serius akibat lemahnya pengelolaan limbah bahan berbahaya dan beracun. Meskipun telah terdapat landasan hukum yang kuat, khususnya melalui Undang-Undang No. 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup serta Peraturan Pemerintah No. 101 Tahun 2014 tentang Pengelolaan Limbah Bahan Berbahaya dan Beracun, lemahnya penegakan mekanisme pertanggungjawaban korporasi dalam praktik justru mempersulit permasalahan tersebut. Oleh karena itu, artikel ini mengkaji tanggung jawab hukum korporasi atas pencemaran lingkungan yang disebabkan oleh limbah bahan berbahaya dan beracun dalam kerangka hukum lingkungan di Indonesia. Dengan menggunakan metode yuridis-empiris melalui pendekatan perundang-undangan, konseptual, dan studi kasus, penelitian ini menganalisis penerapan doktrin hukum seperti polluter pays principle, strict liability, vicarious liability, dan identification theory dalam penegakan tanggung jawab korporasi terhadap pencemaran lingkungan. Hasil penelitian menunjukkan bahwa sebagian besar perusahaan belum mematuhi standar pengelolaan limbah karena lemahnya pengawasan, ketidakjelasan regulasi, dan ketidakkonsistenan sanksi, sehingga pelanggaran lingkungan terus berulang. Hanya sebagian kecil korporasi yang berhasil dimintai pertanggungjawaban secara perdata, administratif, maupun pidana. Dengan demikian, penguatan harmonisasi regulasi, peningkatan efektivitas penegakan hukum, serta integrasi prinsip tanggung jawab korporasi menjadi langkah mendesak dalam mewujudkan tata kelola industri yang berkelanjutan. Pada akhirnya, kerangka pertanggungjawaban yang transparan dan tegas menjadi instrumen penting untuk menegakkan polluter pays principle sekaligus melindungi kesehatan masyarakat dan keberlanjutan ekosistem. Keywords: Corporate Responsibility; Hazardous Waste; Environmental Law; Strict Liability.